2021
DOI: 10.1002/ptr.7060
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Effectiveness of herbal oral care products on ventilator‐associated pneumonia

Abstract: Ventilator-associated pneumonia (VAP) resulting from bacterial infection is a prevalent medical problem in intensive care units (ICUs). The purpose of this study was to systematically review available studies on oral products employed to control and reduce VAP in patients undergoing tracheal intubation. This study was based on a systematic review of clinical trial data from science databases such as PubMed, Cochrane, Scopus, and Web of science. Articles were reviewed and selected according to defined criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our results are similar to some of the findings in a recent systematic review [53]. However, our study showed that Chamomile extract had a significant advantage over CHX in reducing Colony Number (OR: 0.63, 95% CI: 0.46-0.85), but no significant advantage over CHX in reducing the incidence of VAP (OR: 1.15, 95% CI: 0.5-2.79), which is different from the clinical trial results [23].…”
Section: Plos Onesupporting
confidence: 93%
“…Our results are similar to some of the findings in a recent systematic review [53]. However, our study showed that Chamomile extract had a significant advantage over CHX in reducing Colony Number (OR: 0.63, 95% CI: 0.46-0.85), but no significant advantage over CHX in reducing the incidence of VAP (OR: 1.15, 95% CI: 0.5-2.79), which is different from the clinical trial results [23].…”
Section: Plos Onesupporting
confidence: 93%
“…Nevertheless, all studies focused on healthy participants having gingivitis, and no study intervention used mouthwash containing constituents from A. lakoocha . A systematic review of a herbal oral care product in critically ill patients involved 18 studies with more than 10 major natural products that showed the effects of reduction of the oral microbial flora comparable to CHX 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Their medicinal and physical properties make these substances intriguing. Several companies are increasing including herbal compounds in goods as a means of enhancing their medicinal properties (Mojtahedzadeh et al, 2021; Telrandhe et al, 2021). Complementary and alternative medicine (CAM) practitioners and patients are no longer on the fringes of conventional care.…”
Section: Introductionmentioning
confidence: 99%